HUBUNGAN KECERDASAN EMOSIONAL DAN SPIRITUAL DENGAN KUALITAS HIDUP PASIEN KANKER STADIUM LANJUT DI UNIT PELAYANAN ONKOLOGI DAN KEMOTERAPI RSUD PROF. DR. W.Z. JOHANES KUPANG - marlin nau (Cintra Bangsa University - Literacy and Publishing Center (CBU-LPC), 2021)
Cancer provides significant physical and psychological changes to individuals, including sadness, worry and fear for the future. Cancer patients who have negative perceptions of their disease tend to have maladaptive coping. This condition will lead the patient to a bad adaptation process / not accepting himself. This will affect the patient's quality of life in dealing with the disease they are suffering from. The quality of life for cancer patients is influenced by emotional and spiritual intelligence. Purpose to determine the relationship between emotional and spiritual intelligence with the quality of life of advanced cancer patients in the Oncology and Chemotherapy Service Unit of Prof. DR. W.Z. Johanes Kupang. Methods this study is an analytic correlation with a cross sectional design. The sampling technique used was total sampling and the sample was taken by 45 respondents. The statistical test used was the Spearman Rho test. The results: showed that the emotional intelligence of advanced cancer patients at Prof. DR.W.Z. Johanes Kupang has good emotional intelligence as much as 53.3%, good spiritual intelligence as much as 57.8% and good quality of life as much as 68.9%. The results showed that there was a relationship between emotional intelligence and the quality of life of patients with advanced cancer (p = 0.000) in the oncology and chemotherapy service units of Prof. DR. W.Z. Johanes Kupang . There is a relationship between spiritual intelligence and the quality of life of patients with advanced cancer (p = 0.000) in the oncology and chemotherapy service units of Prof. DR. W.Z. Johanes Kupang. It is hoped that the patient can maintain emotional and spiritual intelligence to improve the quality of life. Keywords: Emotional intelligence, spirituality, quality of life, cancer.